Earth economics an introduction to demand management, long-run growth and global economic governance - Bergeijk, Peter A. G. van.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
Taking stock of emerging planet data and analysing policies during the global crisis, Earth Economics provides a comprehensive and accessible introduction to basic macroeconomic concepts, methods and principles, and their application to real world data. Written principally for students seeking an introduction to macroeconomics, this book offers a completely new angle to policy, with a focus on the truly global level. Underpinned by empirical orientation of state-of-the-art data, it introduces earth economics as the study of the economy of our planet from the perspective of an autarkic system (a closed economy), focussing on policymaking that improves global rather than national welfare. Key features include: A discourse on issues fundamental to the understanding of macroeconomics. An introduction to economists tools and concepts. Non-economists will learn how to survive in a discussion with economists: where to ask questions, where to listen, where to skip and where to ignore. Presentation of extensive and wide-ranging data in a consistent and comprehensive framework. In-depth treatment of key concepts including: aggregates, autarky, closed economies, current accounts, earth economics, data, macroeconomics, microeconomics, development and global public goods. Provision of a thorough, working understanding of the subject matter via exercises set throughout the book, including: questions on the text, calculations, formulating arguments and preparation, analysis and interpretation of data and figures. See the companion website www.eartheconomics.info for updates and additional information.
pt. I. Short-term fluctuations and demand management -- pt. II. Long run -- pt. III. Earth governance and global public goods.
Includes bibliographical references and index.
Keywords: Globalization -- Economic aspects; International economic relations; International finance; Electronic books